2008
DOI: 10.1515/jpem.2008.21.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring System in the Screening of Early Glucose Derangements in Children and Adolescents with Cystic Fibrosis

Abstract: Intermediate glucose values during OGTT should be considered as a screening test in patients with CF. CGMS can be useful in studying the early occurrence of glucose derangements in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 20 publications
0
39
0
2
Order By: Relevance
“…Studies have shown a weak correlation between HbA1c and the degree of glucose tolerance. However, when HbA1c yields a high result, it should be taken into consideration in the diagnosis (20,21).…”
Section: Definition and Diagnosis Of Cfrd -An Evolving Visionmentioning
confidence: 99%
“…Studies have shown a weak correlation between HbA1c and the degree of glucose tolerance. However, when HbA1c yields a high result, it should be taken into consideration in the diagnosis (20,21).…”
Section: Definition and Diagnosis Of Cfrd -An Evolving Visionmentioning
confidence: 99%
“…Franzese et al 194 also examined the use of CGMSs, this time in further investigation of PPH. Eighty-seven patients aged > 10 years had OGTTs, and 27 had at least one abnormal intermediate (30,60 or 90 minutes, but details not given) level of > 7.6 mmol/l.…”
mentioning
confidence: 99%
“…Moreover, in selected high-risk adolescents with CF and NGT or IGT, pathological CGMS glucose excursions were reported in around 50-70% of the cases (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…There is now evidence that the OGTT method, evaluating fasting and 2-h postload glucose, may miss episodes of hyperglycaemia. It has been demonstrated recently that the continuous glucose monitoring system (CGMS) is a useful and valid tool in defining glucose metabolism in children and adults affected by CF with early glucose derangements (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%